2014
DOI: 10.1002/eqe.2480
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of shear‐dominated RC columns using the nonlinear truss analogy

Abstract: Summary This paper uses nonlinear truss models for the analysis of shear‐dominated reinforced concrete (RC) columns subjected to cyclic loading. A previously established method, aimed to the analysis of RC walls, is enhanced to allow simulations of column members. The concrete constitutive equations are modified to account for the contribution of the aggregate interlock to the shear resistance. Additionally, an equation is proposed to determine the inclination angle of the diagonal members in the truss models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
(40 reference statements)
0
17
0
1
Order By: Relevance
“…The modulus of elasticity of the concrete is assigned a value of 2f c /ε ο . The parameter M in Equation is calibrated in accordance with Moharrami et al, and the value of λ t is found using the equation by Bažant for the mode‐I fracture energy, G t . The compressive fracture energy, G c , is set equal to 100 G t , based on recommendations by Feenstra .…”
Section: Validation Of Analysis Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The modulus of elasticity of the concrete is assigned a value of 2f c /ε ο . The parameter M in Equation is calibrated in accordance with Moharrami et al, and the value of λ t is found using the equation by Bažant for the mode‐I fracture energy, G t . The compressive fracture energy, G c , is set equal to 100 G t , based on recommendations by Feenstra .…”
Section: Validation Of Analysis Methodologymentioning
confidence: 99%
“…In all analytical models, the Poisson 0 s ratio, v, is set equal to 0. 58 and the value of λ t is found using the equation by Bažant 59 for the mode-I fracture energy, G t . The compressive fracture energy, G c , is set equal to 100G t , based on recommendations by Feenstra.…”
Section: Validation Of Analysis Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…A truss model is idealized by using principal stress trajectories obtained from linear analysis [1]. Nonlinear truss model is established by assignment of location of horizontal elements including longitudinal rebars for beams and diagonal element angles [16]. Truss model herein uses elements in the horizontal, vertical and diagonal directions representing steel reinforcement and concrete areas.…”
Section: Nonlinear Truss Modeling Approachmentioning
confidence: 99%
“…Lu and Panagiotou [15] developed a nonlinear beam-truss modeling approach for modeling RC walls. Moharrami et al [16] enhanced the truss model for analysis of shear-critical RC columns including the contribution of aggregate interlock effects. Lu et al [17] presented a 3-D truss model for structures including walls and slabs with mesh refinement in the bottom story.…”
Section: Introductionmentioning
confidence: 99%